If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(-3)+2x=x-1
We move all terms to the left:
(-3)+2x-(x-1)=0
We add all the numbers together, and all the variables
2x-(x-1)-3=0
We get rid of parentheses
2x-x+1-3=0
We add all the numbers together, and all the variables
x-2=0
We move all terms containing x to the left, all other terms to the right
x=2
| -3x=40=10 | | (-7x)+1=(-8x)+7 | | |x-5|+2=5 | | -4(-7u+6)-9u=5(u-6)-1 | | 10=54-x | | 4x^2+160x-156=0 | | 8+50x=12+25x | | (-5)-5x=(-11)-8x | | 4m+2m+2=3m-7 | | 26x-7+10x+7=180 | | 4(w+7)=8w-4 | | |x-3|+2=5 | | -6+x/5=-41 | | (-6x)+4=(-16)-x | | 2h=25h | | 6y-2(y-2)+5=0 | | 18-1/2(2s+18)=-2s-6 | | -5n=n/2 | | -k-4k=15 | | 49-y=7/36y | | 13p+108=285 | | 2.3x-5+3x+8=19.5 | | x2+9=90 | | (-7)-3x=(-4x)-7 | | 36^7=6^x | | 7p+4=29=2p | | 13p=108 | | 1/2(8x+32)=x^2+4x | | 4x-43+3x=10(3x-2) | | 2w+8=6 | | 3x-4=8(x/5-1) | | 49-y=7/36 |